Geovisualization of the Excavation Process in the Lesvos Petrified Forest, Greece Using Augmented Reality - Ermioni-Eirini Papadopoulou; Vlasios Kasapakis; Christos Vasilakos; Apostolos Papakonstantinou; Nikolaos Zouros; Athanasia Chroni; Nikolaos Soulakellis (ISPRS International Journal of Geo-Information, 2020)
Augmented reality (AR), in conjunction with 3D geovisualization methods, can provide significant support in monitoring geoconservation activities in protected geosites, such as the excavation process in fossil sites. The excavation process requires a monitoring methodology that will provide a complete and accurate overview of the fossils, their dimensions, and location within the different pyroclastic horizons, and the progress of the excavation works. The main purpose of this paper is the development of a user-friendly augmented map application, specifically designed for tracking the position of petrified tree trunks, providing information for their geometric features, and mapping the spatiotemporal changes occurring in the surrounding space. It also aims to probe whether the rapid acquisition of a 4K video can generate cartographic derivatives of petrified findings during a geosite excavation. A database accumulated 2D and 3D cartographic information, while the geovisualization environment displayed the surface alterations, at two scales: a) 1:500 (excavation area) and b) 1:50 (trench level). Unmanned aerial systems (UASs), used for data acquisition in three excavation periods, consisted of two flights at two different altitudes: one to record changes throughout the study area and the other to provide information on trunks at trench level, via a high-resolution (4K) video. Image-based 3D modeling followed, in which image georeferencing was conducted with ground control points (GCPs). Finally, 2D and 3D geovisualizations were created to depict the excavation changes through time. The cartographic products generated at two cartographic scales depicted the spatiotemporal changes of the excavation.